Penerapan Algoritma A* (A-Star) untuk Mencari Rute Terpendek dari Bumi Perkemahan Pramuka Cibubur ke Stadion Gelora Bung Karno - Mutia, Selvi; Lestari, Sri (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LPPM) STMIK Indonesia Banda Aceh, 2024)
Jakarta, with its heavy traffic, has many alternative routes to reach destinations. The Gelora Bung Karno Stadium (GBK) is an iconic sports venue in Indonesia, built in the 1960s and serving as the center for various sports and entertainment events. Although the Cibubur Scout Campground (Buperta) offers outdoor activities, its sports facilities are limited compared to GBK. Residents of Cibubur often face traffic congestion when heading to GBK, especially on weekends. This study aims to apply the A* algorithm to find the shortest and fastest route from Buperta to GBK using Google Maps features. The A* algorithm is chosen for its optimal route search capabilities. The research findings indicate that among the four routes studied (Mayjen Sutoyo Cawang, Dewi Sartika, TB Simatupang, and Lenteng Agung), the Dewi Sartika route is the fastest, with a distance of 15.070 km. The implementation of the A* method is expected to assist the public in finding the fastest route and addressing traffic congestion as well as the lack of knowledge about alternative routes.